Treating nightmares in posttraumatic stress disorder with dronabinol: study protocol of a multicenter randomized controlled study (THC PTSD-trial) - Röpke, Stefan; Schoofs, Nikola; Priebe, Kathlen; Wülfing, Felix; Schmahl, Christian; Röhle, Robert; Zähringer, Jenny; Lotter, Tobias; Otte, Christian; Koglin, Stefanie (BMC psychiatry, 2023)
Distressing nightmares are a core symptom of posttraumatic stress disorder (PTSD) and contribute to psychiatric comorbidity, impaired physical health and decreased social functioning. No specific pharmacological treatment for PTSD-related nightmares is yet approved. Preliminary clinical data indicate that cannabinoid agonists can improve nightmares and overall PTSD symptoms in patients with PTSD. The primary objective of the study is to examine the efficacy of oral dronabinol (BX-1) versus placebo in reducing nightmares in patients with PTSD. The secondary objectives of the study are to examine the efficacy of oral BX-1 in reducing other PTSD symptoms.
Gesehen am 21.06.2023